2017
DOI: 10.1080/09546634.2017.1329511
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 inhibition: role in psoriasis and inflammatory bowel disease

Abstract: Anti-IL-17 medications are associated with IBD exacerbation. Caution should be used in prescribing these medications in patients with diagnosed IBD or personal history suggestive of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
94
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 47 publications
4
94
0
4
Order By: Relevance
“…Four patients on adalimumab developed severe conjunctivitis, miliary tuberculosis, neuroborreliosis, and herpes virus encephalitis, respectively, and five patients experienced paradoxal worsening and exanthematous outbreak of psoriasis. There are reports showing concerns during treatment with IL‐17 class of inhibitors regarding the occurrence of inflammatory bowel disease (IBD) . In our registry, one case of newly diagnosed and endoscopically confirmed Crohn's disease was reported during the treatment with secukinumab.…”
Section: Discussionmentioning
confidence: 95%
“…Four patients on adalimumab developed severe conjunctivitis, miliary tuberculosis, neuroborreliosis, and herpes virus encephalitis, respectively, and five patients experienced paradoxal worsening and exanthematous outbreak of psoriasis. There are reports showing concerns during treatment with IL‐17 class of inhibitors regarding the occurrence of inflammatory bowel disease (IBD) . In our registry, one case of newly diagnosed and endoscopically confirmed Crohn's disease was reported during the treatment with secukinumab.…”
Section: Discussionmentioning
confidence: 95%
“…Этанерцепт способен вы-звать ухудшение течения/активацию ВЗК [2,7,14,49]. Следует соблюдать осторожность при назначении препа-рата секукинумаб пациентам с обострением болезни Кро-на, поскольку в клинических исследованиях наблюдалось усугубление течения болезни Крона, в некоторых случаях тяжелое [63,64].…”
Section: таблицаunclassified
“…Наличие ВЗК у больных АС допускает лечение с использованием только моноклональных антител к ФНОa, I A назначение таким пациентам этанерцепта и иИЛ17А не показано [7,13,49,63,64] 2. Скрининг на наличие активной или латентной туберкулезной инфекции обязателен перед назначением I A любого ГИБП [65,66] 3.…”
Section: таблицаunclassified
“…In a systematic review, the incidence of CD and UC in secukinumab‐treated patients was 110 and 150 per 100 000 patient‐years respectively . This represents a > 10‐fold increase in incidence compared with the background risk of 0.5–10.6 and 0.9–24.3 per 100 000 patient years .…”
mentioning
confidence: 99%
“…IL‐17‐mediated induction of T‐helper (Th)17 lymphocytes is known to be important in triggering IBD, and inhibition of this pathway was expected to treat IBD. A trial of secukinumab for IBD unexpectedly showed worse outcomes in the active treatment arm . In the pivotal AS secukinumab trials, five patients treated with secukinumab developed either de novo colitis or exacerbations of existing colitis …”
mentioning
confidence: 99%